The impact of the cognitive revolution in educational psychology - Royer, James M., 1941- (Emerald Publishing Limited : Information Age Pub., 2005)
The book provides a description of the cognitive revolution which began in the 1950s and reached full fruition in the late 1960s. The term "cognitive revolution" began to be used to take advantage of an analysis of scientific revolutions in general that was developed by Thomas Kuhn. The next section describes how some aspects of the cognitive revolution seem to fit Kuhn's analytic framework, and others do not. Following this analysis the book turns to examining the impact of the cognitive revolution in educational psychology as illustrated by the remaining chapters in the book.
Keywords: Educational psychology -- History.; Cognitive science -- History.; Education -- Educational Psychology.; Educational psychology.; elektronické knihy; electronic books